Exploring the Preparation of Albendazole-Loaded Chitosan-Tripolyphosphate Nanoparticles - Kang, Bong-Seok (Materials (Basel), 2015)
The objective of this study was to improve the solubility of albendazole and optimize the preparation of an oral nanoparticle formulation, using β-cyclodextrin (βCD) and chitosan-tripolyphosphate (TPP) nanoparticles. The solubility of albendazole in buffers, surfactants, and various concentrations of acetic acid solution was investigated. To determine drug loading, the cytotoxic effects of the albendazole concentration in human hepatocellular carcinoma cells (HepG2) were investigated. The formulations were prepared by mixing the drug solution in Tween 20 with the chitosan solution. TPP solution was added dropwise with sonication to produce a nanoparticle through ionic crosslinking. Then the particle size, polydispersity index, and zeta potential of the nanoparticles were investigated to obtain an optimal composition. The solubility of albendazole was greater in pH 2 buffer, Tween 20, and βCD depending on the concentration of acetic acid. Drug loading was determined as 100 µg/mL based on the results of cell viability. The optimized ratio of Tween 20, chitosan/hydroxypropyl βCD, and TPP was 2:5:1, which resulted in smaller particle size and proper zeta positive values of the zeta potential. The chitosan-TPP nanoparticles increased the drug solubility and had a small particle size with homogeneity in formulating albendazole as a potential anticancer agent.